Lung-function trajectories: relevance and implementation in clinical practice - Melén, Erik; Faner, Rosa; Allinson, James P; Bui, Dinh; Bush, Andrew; Custovic, Adnan; Garcia-Aymerich, Judith; Guerra, Stefano; Breyer-Kohansal, Robab; Hallberg, Jenny; Lahousse, Lies; Martinez, Fernando D; et al. (The Lancet (British edition), 2024)
Lung development starts in utero and continues during childhood through to adolescence, reaching its peak in early adulthood. This growth is followed by gradual decline due to physiological lung ageing. Lung-function development can be altered by several host and environmental factors during the life course. As a result, a range of lung-function trajectories exist in the population. Below average trajectories are associated with respiratory, cardiovascular, metabolic, and mental health comorbidities, as well as with premature death. This Review presents progressive research into lung-function trajectories and assists the implementation of this knowledge in clinical practice as an innovative approach to detect poor lung health early, monitor respiratory disease progression, and promote lung health. Specifically, we propose that, similar to paediatric height and weight charts used globally to monitor children's growth, lung-function charts could be used for both children and adults to monitor lung health status across the life course. To achieve this proposal, we introduce our free online Lung Function Tracker tool. Finally, we discuss challenges and opportunities for effective implementation of the trajectory concept at population level and outline an agenda for crucial research needed to support such implementation.